Polemik Arah Kiblat dan Solusinya dalam Perspektif al-Qurâan - lah, Ngami (MILLATI: Journal of Islamic Studies and Humanities, 2016)
Polemics Qibla kept rolling in the middle of the community, and also triggered byÂ the errata Fahwa Indonesian Ulema Council (MUI) number 03 of 2010 on theÂ Qiblah which among dictum states that lies geographically Indonesia is located inÂ the eastern part of the Kaaba/Mecca, the mecca of the people Islam Indonesia isÂ facing westward. Recently, the debate about the direction of Qibla is getting warmedÂ up. Not only in certain areas, but has become a national issue. In determining theÂ Qibla direction, no one tried to find the direction of Qibla to be exactly facing theÂ Kaâaba (âain al-Kaâbah) so it should take a position toward the northwest, and someÂ are found quite facing him alone (jihhah al-ka âbah), namely the west and prayersÂ continue to be valid. Their reality thereby causing confusion among IndonesianMuslims. Given this reality it needed the guidance and explanation can assuage theÂ anxiety of the people. Al-Quran and al-Sunnah be tumpuhan Qibla direction in theÂ resolution of issues among the people. This article by referring to the interpretationÂ and understanding of the verses of the Koran and the Sunna associated with theÂ direction of Qibla, will try to enlighten people to the problems associated withÂ determining the qibla direction